An Exploration of God’s Love in John Calvin’s Theology: Does God Love Everyone or Only the Elect? - Timotius, Timotius (MAHABBAH: Journal of Religion and Education, 2025)
The love of God is a central topic in Christian theology. However, views on the love of God are not always consistent in Christian theology. One well-known theologian who is considered inconsistent in his theology of God’s love is John Calvin. Calvin believed that God chose some people to be saved, which raises questions about whether Calvin truly believed in God’s universal love, since there are those who are not chosen. T.H.L. Parker argued that although Calvin spoke a lot about God’s love, his views often contained inconsistencies in his theology, leading to questions about whether Calvin truly believed in God’s universal love. On the other hand, Richard A. Muller stated that the concept of God’s love in Calvin’s theology is very consistent and not ambiguous. According to him, Calvin viewed God’s love as a love that is not dependent on humans and not limited to those who receive it. God’s love in Calvin’s view is a praiseworthy and noble love because it encompasses all of humanity, both the elect and the non-elect. This article is written to explain the misunderstanding about John Calvin being inconsistent in his theology of God’s love. To answer the above issue, the author will use the literature method. The author will examine all of Calvin’s writings to explain that Calvin is very consistent in his theology of God’s love, so those who consider the theology of God’s love to be inconsistent can clearly see that what is accused of Calvin is not true.